2009
DOI: 10.1007/s12303-009-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal alteration and isotopic variations of igneous rocks in Barton Peninsula, King George Island, Antarctica

Abstract: O, H, S and Sr isotopes were investigated to characterize the nature of hydrothermal fluids and alteration processes in volcanic and intrusive rocks in Barton Peninsula, King George Island. The oxygen and hydrogen isotope compositions of altered basaltic andesite and granodiorite are similar to each other. The δ O and δD values gradually decrease from altered basaltic andesite to altered dyke and quartz-veined volcaniclastic rock. The genetic linkage between hydrothermal fluid and granodiorite intrusion accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The values of 87 Sr/ 86 Sr of volcanics in the Barton Peninsula range from 0.703 314 to 0.703 504, which are similar to those determined in the Fildes Peninsula, King George Island (Machado et al, 2005). Shin et al (2009) reported that the Sr isotope …”
Section: Oxygen and Strontium Isotopessupporting
confidence: 76%
See 1 more Smart Citation
“…The values of 87 Sr/ 86 Sr of volcanics in the Barton Peninsula range from 0.703 314 to 0.703 504, which are similar to those determined in the Fildes Peninsula, King George Island (Machado et al, 2005). Shin et al (2009) reported that the Sr isotope …”
Section: Oxygen and Strontium Isotopessupporting
confidence: 76%
“…3c), significantly lower than the presumed original magmatic values of (-0.8±0.2)‰ (Sakai et al, 1982). Initial Sr isotopic compositions of the volcanic rocks span a narrow range from 0.703 312 to 0.703 504 which are similar to the less altered volcanic rocks reported by Shin et al (2009). These ( 87 Sr/ 86 Sr) i values of volcanic rocks belong to the present midoceanic ridge basalt (Dickin, 2005).…”
Section: Resultsmentioning
confidence: 49%
“…The 87 Sr/ 86 Sr ratios of meltwater, lake and seawater samples range from 0.704554 to 0.707716 with an average of 0.706004 (n = 26), from 0.706274 to 0.709006 with an average of 0.707822 (n = 5), and from 0.709025 to 0.709397 with an average of 0.709186 (n = 3), respectively (Table 1). Previous study showed that rock samples display the 87 Sr/ 86 Sr ratios, ranging from 0.703218 to 0.704620 with an average of 0.703685 (Shin et al, 2009).…”
Section: Strontium and Lithium Isotopesmentioning
confidence: 99%